Resorting to (un)secure(d) Aging - Came, H; Humphries-Kila, Maria (John Wiley & Sons, Inc., 2017)
The commodification of later life by the retirement village industry opens a gated existence to a small portion of the globe’s elderly. Such villages are presented in media images as glamourous and fun-filled life-styles, a consumer choice not unlike the purchase of accommodation at a holiday resort – only more permanent and with a secured channel to the dependency-care that may lie in the future. We offer a critical view of such consumer choice not to diminish the security sought by those who can afford such a purchase, but to examine this depiction for what it illuminates and obscures in the lives of those who have equity to sap and those who do not – exposing to view the deeply institutionalised logic of capitalist markets. Drawing on the traditions of critical theory we hold our focus on the attraction to resort-style communities as a herding of the equity rich, the struggle of many diligent citizens to provide financially for their later years, and the vulnerability of the frail who must rely on state or charitable provision. Such scrutiny exposes contradictions in the view of ‘the market as freedom’ and invites a consideration of who we are as a just people.
Keywords: Ageing; Critical theory; Marginalisation; Privilege; Retirement villages